TEACHER’S STRATEGIES USED TO REDUCE SPEAKING ANXIETY IN ENGLISH CLASSROOM AT SMKN 1 KEDIRI - Hamida, Reka Hani; Riwayatiningsih, Rika; Suhartono, Suhartono (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2024)
This research aims to identify and reduce speaking anxiety among students at SMKN 1 Kediri. The study uses a qualitative research design, employing interviews and observations to gather data from English teachers. The collected data will be analyzed using thematic analysis to identify recurring patterns and themes related to the strategies used by teachers. The study found that there are several ways to reduce anxiety, such as providing examples of speaking English in the classroom and assigning tasks that lead to speaking and writing in various instruments or textbooks. The relationship between emotions and anxiety in foreign language classes affects students' self-esteem and achievement in foreign language learning. The traditional "teaching first, testing then" approach is ineffective, as it often relies on unauthentic activities and lacks valuable data. One method is to ask students to answer in English, which can help them feel more comfortable and confident in their abilities. This method is particularly beneficial for students who frequently interact with teachers or friends while learning English. Another effective way to reduce anxiety is by adding English to textbooks or internships, allowing students to become accustomed to speaking English outside of lessons. The findings of this study provide recommendations for teachers, schools, future researchers, and anyone interested in dealing with speaking anxiety in students. Teachers should be encourage students to interact using English, and provide examples of successful speaking. By following these strategies, teachers can help students overcome speaking anxiety and achieve more productive academic.